2016
DOI: 10.1007/s10995-016-1985-1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Multivitamin Use and Preterm Birth in 24 States, Pregnancy Risk Assessment Monitoring System, 2009–2010

Abstract: Objectives The study objective was to examine the prevalence of maternal multivitamin use and associations with preterm birth (<37 weeks gestation) in the United States. We additionally examined whether associations differed by race/ethnicity. Methods Using the Pregnancy Risk Assessment Monitoring System, we analyzed 2009–2010 data among women aged ≥18 years with a singleton live birth who completed questions on multivitamin use 1 month prior to pregnancy (24 states; n = 57,348) or in the last 3 months of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Consistent with the literature, we found that the use of supplements in general was more prevalent among white women [29, 35], older women [34, 35], those with a higher education level [9, 14, 29] and those with a higher income [15, 24, 29]. Although these characteristics suggest some inequality, their differences were not significant.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with the literature, we found that the use of supplements in general was more prevalent among white women [29, 35], older women [34, 35], those with a higher education level [9, 14, 29] and those with a higher income [15, 24, 29]. Although these characteristics suggest some inequality, their differences were not significant.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike the use of iron salts, the use of folic acid and other vitamins and minerals reflected different user profiles, i.e., white, wealthier and more educated [9, 1316, 26, 35]. This difference could be due to the fact that poorer mothers seek health services later in pregnancy when folic acid would no longer be recommended, whereas mothers with better purchasing power and greater access to information would tend to have a planned pregnancy and, thus, a greater chance of beginning antenatal care (and supplementation) early in T1 [15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal nutrition is a key factor for the health of the mother and for fetal development. Conditions such as preeclampsia, anemia, neural tube defects, depression and cognitive dysfunction are associated with lack of proper intake of folic acid [3,4], iron [5], calcium [6],vitamin D and iodine [7,8]. Poor nutrition during fetal development has long been demonstrated by Barker to have long term effects later in the adult life of the offspring [9].…”
Section: Introductionmentioning
confidence: 99%
“…6,10,12,13,[15][16][17] Overall, these studies found higher medication intake (prescription and/or nonprescription) and dietary supplement use in non-Hispanic white women compared with other racial/ethnic groups in the month before or during pregnancy. 6,7,10,12,[15][16][17][18][19] However, many studies were based on retrospective design with the recall of supplement/medication use after knowledge of birth outcomes, whereas our study is strengthened by its prospective data collection and longitudinal design. The Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Fetal Growth Studies-Singleton cohort is ideal for investigating race/ethnic differences in prenatal supplement and medication use because it is a well-characterized, racially/ethnically diverse, and low-risk cohort of pregnant women without pre-pregnancy chronic conditions, which reduces some of the issues with potential confounding that exist in prior literature.…”
mentioning
confidence: 95%